2000
DOI: 10.1038/sj.onc.1203799
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of intracellular signals via tyrosine 1062 in RET activated by glial cell line-derived neurotrophic factor

Abstract: Glial cell line derived neurotrophic factor (GDNF) signals through a multicomponent receptor complex consisting of RET receptor tyrosine kinase and a member of GDNF family receptor a (GFRa). Recently, it was shown that tyrosine 1062 in RET represents a binding site for SHC adaptor proteins and is crucial for both RAS/mitogen activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3-K)/AKT signaling pathways. In the present study, we characterized how these two pathways diverge from tyrosine 1062, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
185
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(195 citation statements)
references
References 47 publications
9
185
1
Order By: Relevance
“…We and others recently demonstrated that a variety of intracellular signals such as the RAS/MAPK and PI3-K/AKT pathways are transduced through tyrosine 1062 in the carboxy-terminal tail of RET (Hayashi et al, 2000;Segou n-Cariou and Billaud, 2000;De Vita et al, 2000;Besset et al, 2000). In addition, we found that the signaling through tyrosine 1062 is critical for transforming activity of all multiple endocrine neoplasia (MEN) 2 mutant forms of RET Ishiguro et al, 1999;Iwashita et al, 1999Iwashita et al, , 2000.…”
Section: Introductionmentioning
confidence: 64%
“…We and others recently demonstrated that a variety of intracellular signals such as the RAS/MAPK and PI3-K/AKT pathways are transduced through tyrosine 1062 in the carboxy-terminal tail of RET (Hayashi et al, 2000;Segou n-Cariou and Billaud, 2000;De Vita et al, 2000;Besset et al, 2000). In addition, we found that the signaling through tyrosine 1062 is critical for transforming activity of all multiple endocrine neoplasia (MEN) 2 mutant forms of RET Ishiguro et al, 1999;Iwashita et al, 1999Iwashita et al, , 2000.…”
Section: Introductionmentioning
confidence: 64%
“…GDNF stimulation can induce the activation of signaling molecules PI3-K/ Akt, Ras/ERK, and CREB, etc. [35][36][37] . CREB plays a key role in transcriptional regulation of GDNF expression [38] .…”
Section: Discussionmentioning
confidence: 99%
“…These residues can serve as intracellular docking sites to many different SH2 domain-containing proteins, including Src. While Src interacts with Ret at Tyr 981 (Encinas et al, 2004), Tyr 1062 serves as a docking site to most other effectors and triggers the activation of the Ras signaling pathway in the developing enteric nervous system, the developing kidney, and also in neuroblastoma (Worby et al, 1996;Jijiwa et al, 2004;Hayashi et al, 2000). Therefore, we examined whether Gdnf can activate Ras signaling in SSCs (He et al, 2008).…”
Section: Ras Signaling Pathwaymentioning
confidence: 99%